2021
DOI: 10.1097/scs.0000000000007901
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular Vesicles Secreted From Thermal Stress-Induced Adipose-Derived Stem Cells on Bone Regeneration

Abstract: ¸ibu ¨yu ¨k Campus, Bas ¸ibu ¨yu ¨k Mah. Maltepe Bas ¸ibu ¨yu ¨k Yolu Sok. No: 9/2, Maltepe,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…By changing the ambient temperature of cultured cells (42°C and 37°C), it was found that the expression of exosome surface markers CD9 and CD63 in the 42°C group was more significant. It was found that the effect of using heat stress induced adipose-derived stem cell (ADSC) exosomes and using β-tricalcium phosphate (TCP) as carrier for bone regeneration was better than using β-TCP or using ADSCs and β-TCP alone [ 19 ]. Some studies have even collected exosome containing chemokines from heat-stressed adipocytes through the lipid raft-dependent pathway to attract and activate DC and T cells and induce an effective anti-tumor immune response as a new direction of tumor vaccine development.…”
Section: Temperaturementioning
confidence: 99%
“…By changing the ambient temperature of cultured cells (42°C and 37°C), it was found that the expression of exosome surface markers CD9 and CD63 in the 42°C group was more significant. It was found that the effect of using heat stress induced adipose-derived stem cell (ADSC) exosomes and using β-tricalcium phosphate (TCP) as carrier for bone regeneration was better than using β-TCP or using ADSCs and β-TCP alone [ 19 ]. Some studies have even collected exosome containing chemokines from heat-stressed adipocytes through the lipid raft-dependent pathway to attract and activate DC and T cells and induce an effective anti-tumor immune response as a new direction of tumor vaccine development.…”
Section: Temperaturementioning
confidence: 99%
“…By changing the ambient temperature of cultured cells (42°C and 37°C), it was found that the surface markers CD9 and CD63 were more significantly expressed in the 42°C group. And that bone regeneration experiments using heat stress-induced ADSC-Exo with β-TCP (tricalcium phosphate) as a carrier were more effective than using β-TCP alone or using the ADSC with β-TCP ( Akdeniz-Dogan et al, 2021 ).…”
Section: Regulators Of Msc-exos Productionmentioning
confidence: 99%
“…Studies investigating exosomes derived from uMSCs that have been pre-differentiated down the osteogenic lineage in vitro prior to EV harvest, also induce bone regeneration when seeded into rat radial bone defect (158). EVs obtained from adipose tissue-derived MSCs (AD-MSCs) have successfully stimulated osteogenic differentiation in murine mouse models in vivo (159,160), although recent studies have indicated the regenerative potential of AD-MSC-EVs has similar potency to transplanted AD-MSCs (161). Recent in vitro studies have highlighted the ability of exosomes secreted by hAD-MSCs, combined with PLAbased scaffolds, to stimulate the osteogenic commitment of hAD-MSCs (162).…”
Section: Utilizing Evs For Bone Regenerative Medicinementioning
confidence: 99%